Estudo da ação de Persea americana Mill. na consolidação de fratura ossea em ratos - MENDONÇA, Priscylla Gouveia (2021)
Abstract: Treatments for bone fractures have improved in recent years, but some still show consolidation disorders. The most frequent open fractures occur in the tibia, with prevalence ranging from 20-40% of cases. The increasing use of natural products, mainly medicinal plants and compounds related to phytopharmaceutical studies, explain the existence of a wide scope for the development of new drugs, particularly of vegetable origin to treat pathologies and associated conditions. Objectives: To evaluate the effectiveness of the administration of hydroethanolic extract of the leaves of Persea Americana Mill. in the consolidation of tibial fractures in rats submitted or not to physical activity. Methodology: Five experimental groups with 6 animals. Healthy Group (H): Without intervation; Fracture + Extract (EF): Induced fracture and oral EHPA; Fracture + Extract + Swimming (SEF): Induced fracture, EHPA and 30 min of daily swimming; Fracture + Swimming (SF): Induced fracture, swimming for 30 min; and Fracture (F): Induced fracture. The dose of 750mg/kg EHPA administered by oral gavage 28 days. Results: Through characterization using the liquid chromatographjy dereplication technique coupled to the mass spectrometry of the extract of Persea Americana Mill. we identified 24 substances, ionized in positive and negative mode, 17 already described in the literature. Behavioral parameters, radiological effects and histology of bone tissue stained with hamatoxylin and eosin are better in groups treated with EHPA(750mg/kg). Histology of the spleen, liver and kidney did not show pathological changes and the dose administered did not induce toxicity.